Description and predictors of hospital costs of oesophageal cancer during the first year following diagnosis in Northern Ireland. (31st January 2013) - Agus, A.M.; Kinnear, H.; O'Neill, C.; McDowell, C.; Crealey, G.E.; Gavin, A.
Abstract : The cost‐effectiveness of novel interventions in the treatment of cancer is well researched; however, relatively little attention is paid to the cost of many aspects of routine care. Oesophageal cancer is the ninth most common cancer in the UK and sixth most common cause of cancer death. It usually presents late and has a poor prognosis. The hospital costs incurred by oesophageal cancer patients diagnosed in Northern Ireland in 2005 ( n = 198) were determined by review of medical records. The average cost of hospital care per patient in the 12 months from presentation was £7847. Variations in total hospital costs by age at diagnosis, gender, cancer stage, histological type, mortality at 1 year, co‐morbidity count and socio‐economic status were analysed using multiple regression analyses. Higher costs were associated with earlier stages of cancer and cancer stage remained a significant predictor of costs after controlling for cancer type, patient age and mortality at 1 year. Thus, although early detection of cancer usually improves survival, this would mean increased costs in the first year. Deprivation achieved borderline significance with those from more deprived areas having lower resource consumption relative to the more affluent.